Gene expression profiles of human granulosa cells treated with bioequivalent doses of corifollitropin alfa (CFA) or recombinant human follicle-stimulating hormone (recFSH). (3rd July 2019) - Sacchi, Sandro; Tenedini, Elena; Tondelli, Debora; Parenti, Sandra; Tagliasacchi, Daniela; Xella, Susanna; Marsella, Tiziana; Tagliafico, Enrico; La Marca, Antonio
Abstract: Using recombinant DNA technologies, a chimeric gene containing the coding sequences of follicle stimulating hormone (FSH) β-subunit and C-terminal peptide of the human chorionic gonadotrophin (hCG) β-subunit have been designed to generate a new gonadotrophin named corifollitropin alfa (CFA). CFA has longer elimination half-life and slower rate of absorption compared with FSH, which makes CFA a long-acting hormone employed as a substitute of the recombinant FSH (recFSH) in the controlled ovarian stimulation (COS). The purpose of this study is to compare the gene expression profiles elicited by bioequivalent doses of CFA or recFSH in primary cultures of human granulosa cells (hGCs). Gonadotrophins exert their functions by binding FSH receptors (FSHRs), activating signaling pathways that increase the cyclic adenosine monophosphate (cAMP) intracellular content. Bioequivalence has been defined as the dose/duration of gonadotrophin treatment able to promote the same amount of intracellular cAMP. hGCs were treated with different doses of either gonadotrophin and the cAMP was measured after different incubation times to establish the bioequivalence. Results obtained by comparing the bioequivalent treatments, showed that CFA is more effective than recFSH in inducing aromatase gene expression after 6 and 24 h from the initial stimulation in agreement with its long-acting characteristic.